Transforming Indonesia’s Legal System: A Diversity, Equity, Inclusion, and Sustainability (DEIS) Perspective - Neneng Yuhelmi Zajilah; Marhaeni Ria Siombo (Indonesian Journal Publisher, 2026)
Indonesia’s legal system faces structural limitations in responding to complex global transformations, including climate crisis, digitalization, and intensified resource extraction, which expose the inadequacy of its predominantly formalistic and sector-based paradigm. This study critically examines the transformation of Indonesia’s legal system through the lens of Diversity, Equity, Inclusion, and Sustainability (DEIS) as a normative and analytical framework. Employing a normative juridical method with statutory and conceptual approaches, this research interrogates constitutional mandates, sectoral legislation, and contemporary legal practices. The analysis reveals a persistent disjunction between constitutional guarantees particularly regarding indigenous rights and environmental protection and their implementation within extractive governance regimes. The Maba Sangaji case is deployed as a critical lens to demonstrate how legal instruments, such as Article 162 of the Mining Law, function to legitimize the criminalization of indigenous resistance while insulating corporate interests. This reflects a deeper structural bias embedded within the current legal paradigm. The study argues that integrating DEIS principles requires not merely regulatory adjustment but a paradigmatic shift that reconfigures legal substance, institutional practices, and legal culture. Such transformation is essential to realign Indonesia’s legal system with constitutional justice, democratic participation, and ecological sustainability in the context of global change.